Distinct pacing profiles result in similar perceptual responses and neuromuscular fatigue development: Why different "roads" finish at the same line?. Issue 7 (3rd July 2022) - Azevedo, Rafael de Almeida; Silva-Cavalcante, Marcos David; Cruz, Ramon; Couto, Patrícia; Lima-Silva, Adriano E.; Bertuzzi, Romulo
ABSTRACT: The current study analysed the effect of distinct pacing profiles (i.e. U, J, and inverted J) in the perceptual responses and neuromuscular fatigue (NMF) development following a 4-km cycling time trial (TT). Twenty-one cyclists with similar training status were allocated into three different groups based on their pacing profile spontaneously adopted during TT. Rating of perceived exertion (RPE), oxygen uptake (⩒O2 ) and heart rate (HR) were continuously recorded. NMF was assessed by using isometric maximal voluntary contractions (IMVC), while the central [i.e. voluntary activation (VA)] and peripheral fatigue of knee extensors [i.e. peak torque of potentiated twitches (TwPt)] were evaluated using electrically evoked contractions performed pre and 2 min after the TT. TT performance was not different amongst pacing profiles (U = 377 ± 20 s; J = 392 ± 23 s; J-i = 381 ± 20 s) (all P > 0.05). RPE, ⩒O2 and HR increased similarly throughout the TT regardless the pacing strategy (all P > 0.05). Similarly, IMVC (U = −9.9 ± 8.8; J = −9.6 ± 4.5%; J-i = −13.8 ± 11.3%), VA (U = −2.3 ± 1.7%; J = −5.4 ± 2.2%; J-i = −6.4 ± 4.5%) and TwPt (U = −32.5 ± 12.0%; J = −29.5 ± 8.0%; J-i = −33.6 ± 13.6%) were similar amongst pacing profiles (all P > 0.05). Therefore, endurance athletes with similar training status showed the same perceived responses and NMF development regardless the pacing profile spontaneously adopted. It was suggested that these responses occurred in order to preserve a similar rate of change in systemic responses (i.e. RPE, ⩒O2 and HR) and NMF development, ultimately resulting in same TT performance. Highlights: Different pacing profiles resulted in the same performance in a 4-km cycling time trial. The similar performance might be due to achievement of the same sensory tolerance limit. There was no difference for perceptual, metabolic and neuromuscular fatigue responses.